Trade shocks, fertility, and marital behavior - Osea Giuntella; Lorenzo Rotunno; Luca Stella (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2021)
Using longitudinal data from the German Socio-Economic Panel, we analyze the effects of exposure to trade on the fertility and marital behavior of German workers. We find that individuals working in sectors that were more affected by import competition from Eastern Europe and suffered worse labor market outcomes were less likely to have children. In contrast, workers in sectors that benefited from increased exports had better employment prospects and higher fertility. These effects are driven by low-educated and married men, and reflect changes in the likelihood of having any child (extensive margin). While among workers exposed to import competition there is evidence of some fertility postponement, we find a significant reduction of completed fertility. There is instead little evidence of any significant effect on marital behavior.
Keywords: F14; F16; J13; 330; International Trade; Labor Market Outcomes; Fertility; Marriage